El cuarto de atrás - Martín Gaite, Carmen; Martín Garzo, Gustavo, 1948- (Madrid : Siruela, 2010)
Madrid, Spain. Some time after the death of Franco, Carmen searches for personal identity after living through the Franco era when everything was frozen--time, dreams, freedom.
El hombre descalzo -- El sombrero negro -- Ven pronto a Cúnigan -- El escondite inglés -- Una maleta de doble fondo -- La isla de Bergai -- La cajita dorada.
Premio Nacional de Literatura, 1978
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Fascism -- Fiction; Spain -- History -- 20th century -- Fiction; Spain -- Politics and government -- 1939-1975 -- Fiction; Spain -- Politics and government -- 1975-1982 -- Fiction; Electronic books